Controlling scaffold conductivity and pore size to direct myogenic cell alignment and differentiation. Issue 10 (28th June 2022) - Basurto, Ivan M.; Muhammad, Samir A.; Gardner, Gregg M.; Christ, George J.; Caliari, Steven R.
Abstract: Skeletal muscle's combination of three‐dimensional (3D) anisotropy and electrical excitability is critical for enabling normal movement. We previously developed a 3D aligned collagen scaffold incorporating conductive polypyrrole (PPy) particles to recapitulate these key muscle properties and showed that the scaffold facilitated enhanced myotube maturation compared with nonconductive controls. To further optimize this scaffold design, this work assessed the influence of conductive polymer incorporation and scaffold pore architecture on myogenic cell behavior. Conductive PPy and poly(3, 4‐ethylenedioxythiophene) (PEDOT) particles were synthesized and mixed into a suspension of type I collagen and chondroitin sulfate prior to directional freeze‐drying to produce anisotropic scaffolds. Energy dispersive spectroscopy revealed homogenous distribution of conductive PEDOT particles throughout the scaffolds that resulted in a threefold increase in electrical conductivity while supporting similar myoblast metabolic activity compared to nonconductive scaffolds. Control of freezing temperature enabled fabrication of PEDOT‐doped scaffolds with a range of pore diameters from 98 to 238 μm. Myoblasts conformed to the anisotropic contact guidance cues independent of pore size to display longitudinal cytoskeletal alignment. The increased specific surface area of the smaller pore scaffolds helped rescue the initial decrease in myoblast metabolic activity observed in larger pore conductive scaffolds while also promoting modestly increased expression levels of the myogenic marker myosin heavy chain (MHC) and gene expression of myoblast determination protein (MyoD). However, cell infiltration to the center of the scaffolds was marginally reduced compared with larger pore variants. Together these data underscore the potential of aligned and PEDOT‐doped collagen scaffolds for promoting myogenic cell organization and differentiation.